Evaluation of the Sleep Disorders in patients submitted to Polissomnography (Research, Society and Development, 2021)
Objective: To characterize the sleeping disturbs of patients submitted to a polysomnography and establish their associations with epidemiological ranges. Methods: Transversal study, observational, conducted by analyzing data of 101 patients submitted to polysomnography at the Laboratory of Sleep Medicine of HUMAP, Campo Grande, MS, Brazil. The data used were the polysomnography itself and patronized grades (somnolence scale of Epworth and Berlin Questionnaire). Results: The high risk for Syndrome of Obstructive Sleep Apnea (SOSA) was identified in 83% of the evaluated patients. About the polysomnographic results, 77% were diagnosed with SOSA, being most of them female. In the patients with SOSA, 95,5% were obese or overweighed. The excessive daytime sleepiness was detected in 51,2% of the patients diagnosed with SOSA. Conclusion: The prevalence of sleeping disorders was high, being the patients that were diagnosed with SOSA most of them female, with a bigger SED frequency, overweighed and obese and with high blood pressure. These were relevant risk factors for a respiratory syndrome.